Anorexia y bulimia entre el sujeto y el otro (2012)
ABSTRACT: Anorexia and bulimia, as clinical phenomena that have been preponderados in our contemporary world, deriving themselves various edges and various render modes that make that range "psi" has an array of approaches that much said but little explained, reducing such phenomena as determined by conditions social. This, in the field of psychoanalysis however seems to be also different modes of approach; all in vain because such interpretations are insufficient since it does not recognize that the Lacanian clinic it is an approach to the always particular structure, which cannot be understood but to the extent that the signifier affects the living body, allowing the advent of a subject in the place of another. In other words; the approach of anorexia and bulimia is only possible where psychoanalysis as praxis, deals with the real by the symbolic.